2019
DOI: 10.32457/ijmss.2019.037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the intensive care unit (ICU) admissions in the Benue State University Teaching Hospital.

Abstract: Today, intensive care units (ICUs) of most hospitals in developed countries have become separate departments staffed by career intensive care physicians or intensivists from various fields of medicine. In Nigeria, however, ICUs are still part of the anaesthesia department and critical care constitutes a significant part of the workload and responsibilities of anesthetists. This study was carried out to ascertain the types of disease conditions that were brought into the ICU for management at the Benue State Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Intensive care units (ICUs) were established in the mid-1900s [ 1 , 2 ]. With advances in life-saving interventions, survival improved over the past decades, positively impacting a large number of patients [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive care units (ICUs) were established in the mid-1900s [ 1 , 2 ]. With advances in life-saving interventions, survival improved over the past decades, positively impacting a large number of patients [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the Society of Critical Care Medicine (SCCM) convened an international multistakeholder group that created the term "Post-Intensive Care Syndrome" (PICS). PICS was created with multiple objectives, including: (1) to raise awareness among clinicians, patients/families and the general public, (2) to increase screening for specific impairments occurring after critical illness, (3) to facilitate further research into specific morbidities [4]. More specifically, PICS was defined "as new onset or worsening of impairment(s) in physical, cognitive, and/or mental health that arose after the ICU and persisted beyond hospital discharge" [4].…”
Section: Introductionmentioning
confidence: 99%
“…Common conditions that are treated in ICUs include severe neurological, cardiac, and respiratory diseases [ 3 ]. A study that characterized the ICU admissions in Benue State University Teaching Hospital, Nigeria reported that the most frequent reasons for admissions were post-laparotomy care (24.8%), head injury (18.4%), and burns (11.2%) [ 4 ]. Another study conducted in southeast Nigeria among patients admitted into the ICU of the University of Nigeria Teaching Hospital, Enugu, Nigeria similarly reported postoperative cases (49.3%) as the most common reason for ICU admission, and traumatic brain injury as a leading diagnosis (70.9%) among neurosurgical patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%